Rapport social de service, client et valeur - Philippe Zarifian (La Nouvelle Revue du Travail)
The text develops two ideas. The first is that it is possible to talk about “service-based social relationships” using the full meaning of the concept of a “social relationship” and accepting all of its implications while continuing to differentiate it from the “service relationship” construct. The second, which stems from the first, is that it is possible to talk about a “composition” based on different social relationships that cannot be reduced to one another. By so doing, what becomes apparent is that a composition does exist between a service-based social relationship and the capital-labour nexus. This is instructive as regards service production employment and situates customers’ roles in a different framework than one grounded in a “service relationship” construct.